2019
DOI: 10.3390/molecules24030419
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Smell Like What They Eat: Analysis of Volatile Organic Compounds of Malassezia furfur in Growth Media Supplemented with Different Lipids

Abstract: Malassezia furfur is part of the human skin microbiota. Its volatile organic compounds (VOCs) possibly contribute to the characteristic odour in humans, as well as to microbiota interaction. The aim of this study was to investigate how the lipid composition of the liquid medium influences the production of VOCs. Growth was performed in four media: (1) mDixon, (2) oleic acid (OA), (3) oleic acid + palmitic acid (OA+PA), and (4) palmitic acid (PA). The profiles of the VOCs were characterized by HS-SPME/GC-MS in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 74 publications
3
20
1
Order By: Relevance
“…These compounds were particularly produced by a phylogenetically related subset of Bacillus strains, i.e. strains from clade A and B, whereas they were absent or only produced in low amounts by strains belonging to clade C to clade F. However, it is important to note that the compounds detected in this study were only tentatively identified through GC-MS analysis and that the precise composition of volatile blends emitted by microorganisms may depend on the nutrient medium used to cultivate them (Gonzalez et al 2019). GC peak enhancement with co-injection of authentic standards should be performed to achieve absolute identification of the compounds and analyses ideally should be repeated for different media to investigate how culturing conditions affect the composition of mVOC blends and associated response of parasitoids.…”
Section: Phylogenetic Conservatism Of Mvoc Profilesmentioning
confidence: 73%
“…These compounds were particularly produced by a phylogenetically related subset of Bacillus strains, i.e. strains from clade A and B, whereas they were absent or only produced in low amounts by strains belonging to clade C to clade F. However, it is important to note that the compounds detected in this study were only tentatively identified through GC-MS analysis and that the precise composition of volatile blends emitted by microorganisms may depend on the nutrient medium used to cultivate them (Gonzalez et al 2019). GC peak enhancement with co-injection of authentic standards should be performed to achieve absolute identification of the compounds and analyses ideally should be repeated for different media to investigate how culturing conditions affect the composition of mVOC blends and associated response of parasitoids.…”
Section: Phylogenetic Conservatism Of Mvoc Profilesmentioning
confidence: 73%
“…This suggests that Malassezia VOCs production is stimulated by the compounds in the growth media, demonstrating once again the dynamic metabolism in this yeast. Also, the results showed the decrease in volatile production in a medium supplemented with palmitic acid in which the alkanes were predominant (Gonzalez et al 2019).…”
Section: Vocs Produced By Malassezia Spp How Much Do We Know?mentioning
confidence: 94%
“…Studies about the interaction type microbe-host-insect have been conducted. It has been reported that VOCs from bacteria belonging to human microbiota like Staphylococcus sp., Corynebacterium sp., Bacillus sp., produce certain volatiles that attract malaria mosquitoes (Verhulst et al 2009(Verhulst et al , 2010, and they have been reported also in the yeast Malassezia furfur (Gonzalez et al 2019). Further analyzes are necessary to elucidate the role of these VOCs for Malassezia in the interaction between fungi-host-insect.…”
Section: Vocs Produced By Bacteria/fungi and Their Role In Interactional Processesmentioning
confidence: 99%
See 2 more Smart Citations